The power of promises : rethinking Indian treaties in the Pacific Northwest - Harmon, Alexandra, 1945- (Emil and Kathleen Sick lecture-book series in western history and biography., 2008)
"Treaties with Native American groups in the Pacific Northwest have had profound and long-lasting implications for land ownership, resource access, and political rights in both the United States and Canada. In The Power of Promises, a distinguished group of scholars, representing many disciplines, discuss the treaties' legacies.